Preoperative serum levels of ca 72-4, cea, ca 19-9, and Alpha-fetoprotein in patients with gastric cancer - Mattar, Rejane; Andrade, Claudio Roberto Alves de; DiFavero, Giovanni Mastrantonio; Gama-Rodrigues, Joaquim José; Laudanna, Antonio Atílio (Revista do Hospital das Clínicas, 2002)
INTRODUCTION: The clinical importance of preoperative serum levels of CA 72-4, carcinoembryonic antigen (CEA), CA 19-9, and alpha-fetoprotein (AFP) was prospectively evaluated in 44 patients with gastric cancer. METHOD: The serum tumor marker levels were determined by commercial radioimmunoassay kits. Positivity for CA 72-4 (>;4 U/mL), CEA (>;5 ng/mL), CA 19-9 (>;37 U/mL), and AFP (>;10 ng/mL) were correlated according to the stage, histology, and lymph node metastasis. RESULTS AND DISCUSSION: CA 72-4 showed a higher positivity rate for gastric cancer (47.7%) than CEA (25%), CA 19-9 (25%), and AFP (0%). The combination of CA 72-4 with CEA and CA 19-9 increased the sensitivity to 61.4%. The positivity rates of CA 72-4 in patients at stages I and II (initial disease) and in patients at stages III and IV (advanced disease) were 9% and 60.6%, respectively (P < 0.005). No correlation was found between CEA and CA 19-9 levels and the stage of gastric cancer. There was a tendency of positivity for CA 72-4 to suggest lymph node involvement, but it was not significant (P = 0.075). Serum levels of tumor markers did not show a correlation with the histological types of gastric cancer. CONCLUSION: Preoperative serum levels of CA 72-4 provided a predictive value in indicating advanced gastric cancer.